2010
DOI: 10.1093/sysbio/syq085
|View full text |Cite
|
Sign up to set email alerts
|

Improving Marginal Likelihood Estimation for Bayesian Phylogenetic Model Selection

Abstract: The marginal likelihood is commonly used for comparing different evolutionary models in Bayesian phylogenetics and is the central quantity used in computing Bayes Factors for comparing model fit. A popular method for estimating marginal likelihoods, the harmonic mean (HM) method, can be easily computed from the output of a Markov chain Monte Carlo analysis but often greatly overestimates the marginal likelihood. The thermodynamic integration (TI) method is much more accurate than the HM method but requires mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
881
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 935 publications
(894 citation statements)
references
References 25 publications
7
881
3
3
Order By: Relevance
“…Bayes factors are used in Bayesian model selection to determine which parameter configurations provide the best fit to the data and are equal to twice the difference in marginal loglikelihoods between models (Kass and Raftery, 1995). Following phylogenetic analyses, I then estimated the marginal log-likelihood of each model using the stepping-stone sampling method (Xie et al, 2010) with 50 steps and powers of β corresponding to quantiles of a Beta(0.5, 1.0) distribution. Parsimony-based calculations were performed using PAUP* 4.0a147 (Swofford, 2002).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Bayes factors are used in Bayesian model selection to determine which parameter configurations provide the best fit to the data and are equal to twice the difference in marginal loglikelihoods between models (Kass and Raftery, 1995). Following phylogenetic analyses, I then estimated the marginal log-likelihood of each model using the stepping-stone sampling method (Xie et al, 2010) with 50 steps and powers of β corresponding to quantiles of a Beta(0.5, 1.0) distribution. Parsimony-based calculations were performed using PAUP* 4.0a147 (Swofford, 2002).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Unlike the other model comparison approaches (likelihood ratio test [LRT], Akaike Information Criterion [AIC], and Bayesian Information Criterion [BIC], etc. ), BF calculates the ratio of the marginal likelihood of two models, which has the advantage of taking into account priors used in Bayesian analyses (Xie et al, 2011). The marginal likelihood values of these two competing models (Model 1, Model 2) were estimated using recently developed techniques including path sampling (PS, Lartillot and Philippe, 2006) and stepping-stone sampling (SS, Xie et al, 2011), which have previously demonstrated to have better performance than the harmonic mean estimator (HME, Newton and Calculations of PS and SS were performed in BEAST v 1.7.4.…”
Section: Species Delimitationmentioning
confidence: 99%
“…), BF calculates the ratio of the marginal likelihood of two models, which has the advantage of taking into account priors used in Bayesian analyses (Xie et al, 2011). The marginal likelihood values of these two competing models (Model 1, Model 2) were estimated using recently developed techniques including path sampling (PS, Lartillot and Philippe, 2006) and stepping-stone sampling (SS, Xie et al, 2011), which have previously demonstrated to have better performance than the harmonic mean estimator (HME, Newton and Calculations of PS and SS were performed in BEAST v 1.7.4. First, we ran species tree analyses in * BEAST based on Model 1 and Model 2 respectively, using the same phased dataset for phylogenetic inference including all three lineages of Euprepiophis and five outgroup species.…”
Section: Species Delimitationmentioning
confidence: 99%
See 1 more Smart Citation
“…to the data, whereas likelihood based or point estimators such as Akaike information criteria (AIC) [33] or Bayesian information criteria (BIC) [34] base their decisions on the best fit of each competing model [35]. The use of the marginal likelihood also automatically penalizes the complexity of the model because complex models spread their probability mass widely by predicting various possible outcomes, hence the probability of actual data will be smaller for overly complex models.…”
Section: Stage Ii: Parameterizing the Distribution Of Configuration Tmentioning
confidence: 99%